Evaluasi Pelaksanaan Program Terminal Parkir Elektronik (TPE) dalam Meningkatkan Pendapatan Asli Daerah di Kota Bandung - Bela Puji Utami; Atik Rochaeni Rochaeni; Lukman Munawar Fauzi (Journal of Administration, Governance, and Political Issues, 2025)
This study evaluates the implementation of the Electronic Parking Terminal (TPE) Program in Bandung City and its effectiveness in enhancing local revenue (PAD) from parking retribution. The research aims to assess the extent to which TPE improves efficiency, transparency, and accountability in parking management. Using a descriptive qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model, data were collected through interviews, observations, documentation, and literature review. The findings show that although TPE was designed to reduce revenue leakage and illegal parking practices, its implementation has not yet achieved optimal outcomes. In the context dimension, social readiness and community adaptation to digital systems remain limited. From the input perspective, uneven machine distribution, frequent malfunction, and insufficient training for parking attendants hinder operational performance. In the process dimension, low digital literacy, technical issues, and weak supervision result in continued reliance on manual transactions. In terms of product, TPE contributes positively to transparency and accountability, yet its impact on increasing PAD remains below government targets. The study concludes that while TPE holds promising potential, significant improvements in infrastructure, human resources, and regulatory enforcement are required. Future research should adopt comparative and quantitative approaches to better measure financial impacts and deepen understanding of community behavior toward digital parking innovations.